2016
DOI: 10.1542/hpeds.2015-0229
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Imaging Findings in Young Infants With Bacteremic Urinary Tract Infection

Abstract: Although RUS and VCUG abnormalities were common in this cohort, the frequency and severity were similar to previous studies of infants with UTIs in general. Our findings do not support special consideration of bacteremia in imaging decisions for otherwise well-appearing young infants with UTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
3
12
0
1
Order By: Relevance
“…In the multicenter study of 251 infants <3 months old with bacteremic UTIs, the prevalence of grade IV-V VUR was 12.1%. 31 This is higher than that of the nonbacteremic infants in Honkinen et al's study 32 but more similar to the prevalence of grade IV-V VUR found in Tsai et al (8.2%) and Ismaili et al's (7.0%) studies of UTIs in general. 29,33 There does appear to be a higher prevalence of urinary tract abnormalities in young infants with non-E. coli vs E. coli UTIs.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…In the multicenter study of 251 infants <3 months old with bacteremic UTIs, the prevalence of grade IV-V VUR was 12.1%. 31 This is higher than that of the nonbacteremic infants in Honkinen et al's study 32 but more similar to the prevalence of grade IV-V VUR found in Tsai et al (8.2%) and Ismaili et al's (7.0%) studies of UTIs in general. 29,33 There does appear to be a higher prevalence of urinary tract abnormalities in young infants with non-E. coli vs E. coli UTIs.…”
supporting
confidence: 63%
“…29,33 There does appear to be a higher prevalence of urinary tract abnormalities in young infants with non-E. coli vs E. coli UTIs. 31,32,34,35 The odds of an abnormal VCUG was 8.0 (95% CI: 2.3-28) times higher for non-E. coli than E. coli UTIs in the study of 251 bacteremic infants. 31 In a study of 122 infants <3 months old, the odds of grade III-V VUR was 10 (95% CI 2.6-41) times higher for non-E. coli than E. coli UTIs.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Bladder wall thickness and bladder debris have been reported as significant imaging findings of UTI in infants younger than three months of age with bacterial UTI in an other study (14).…”
Section: Discussionmentioning
confidence: 74%
“…Bir başka çalışmada, mesane duvarı kalınlığı ve mesane debrisi bakteriyel İYE'li üç aydan daha küçük süt çocuklarında anlamlı görüntüleme bulguları olarak kaydedilmiştir (14).…”
Section: Discussionunclassified